Letters from the Greatest Generation : Writing Home in WWII - Snyder, Shirley A.; Peckham, Howard H. (Howard Henry), 1910-1995 (Book collections on Project MUSE., 2016)
A collection of personal letters from overseas that reveal in day-to-day detail what it was like to serve in World War II. Recounting victory and defeat, love and loss, this is a remarkable and frank collection of World War II letters penned by American men and women serving overseas. Here, the hopes and dreams of the greatest generation fill each page, and their voices ring loud and clear. "It's all part of the game but it's bloody and rough," writes one soldier to his wife. "Wearing two stripes now and as proud as an old cat with five kittens," remarks another. Yet, as many countries rejoiced on V-E Day, this book reveals that soldiers were "too tired and sad to celebrate." Filled with the everyday thoughts of these fighters, the letters are by turns heartbreaking and amusing, revealing and frightening. While visiting a German concentration camp, one man wrote, "I don't like Army life but I'm glad we are here to stop these atrocities." Meanwhile, in another letter a soldier quips, "I know lice don't crawl so I figured they were fleas." A fitting tribute to all veterans, this book brings the experience of war-its dramatic horrors, its dreary hardships, its desperate hope for a better future-to vivid life. "An intimate portrait of the mundane and remarkable, of heroism and terror, of friendship and loss ... Timely, compelling, and important reading."--Matthew L. Basso, author of Men at Work.